Дневник свекрови: роман / Мария Метлицкая - Метлицкая Мария (За чужими окнами. Проза М. Метлицкой, 2013)
Экземпляры: (20131021) / Инвентарный номер: 48634 / Цена: 184.80 / Сис.шифр: Р2 48634 / Авт.знак: М 54 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6